Estudio de la influencia de distintos sustratos de cultivo en el crecimiento y desarrollo en vivero de plantas de ilex l., Q. SUBER L., P. PINA S TER AIT. y P. HALEPENSIS MILL. - Zazo Muncharaz, J; FRANCISCO CASADO, Ma S; TALLÓN MEDRANO, F (II Congreso Forestal Español, 1997)
The influence on various attributes and morphological and anatomical characteristics of seedlings of the mentioned species, of different formulations of growing media commonly used in nurseries, that have fertilized peat as base component and different percentages of pedite, vermiculite, pine bark and sand as ancillary or aeration components, and using the same container, is studied. The obtained results can be applied to propose growing media and cultivation techniques for production of morphological and anatomical quality plants of the mentioned species.
Keywords: Growing medium; Nursery; Plant quality